2013
DOI: 10.11646/zootaxa.3731.2.4
|View full text |Cite
|
Sign up to set email alerts
|

First zoeal stage of ?Cataleptodius parvulus (Fabricius, 1793) and Xanthodius denticulatus (White, 1848) (Decapoda: Brachyura): larval evidences and systematic position

Abstract: The first zoeal stages of ?Cataleptodius parvulus and Xanthodius denticulatus are described and compared with zoeae of other members of the subfamily Xanthinae. The larvae of ?C. parvulus and X. denticulatus differ mainly in: 1) spinulation of rostral and dorsal spines; 2) type of antenna; 3) setation of the basis of first maxilliped; and 4) type of telson. Features common to both species include a carapace provided with well-developed spines on the dorsal (1), rostral (1), and lateral (2) portions; and the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Marques et al, 2003;Barros-Alves et al, 2013;Guerao et al, 2014). According to phylogenetic analysis, Clark and Ng (2010) suggested that the genera Domecia, Quadrella Dana, 1851, Tetralia Dana, 1851and Trapezia Latreille, 1828 are nested in one clade that is defined by the absence of seta 3.5 and seta 3.4 on the third endopodal segment of the second maxilliped (for details, see Clark and Guerao, 2008), and should be according to a synapomorphy defines the Domecia + Tetralia + Trapezia clade: the presence of one subterminal seta on the distal endopod segment of the maxillule (vs. two subterminal setae).…”
Section: Discussionmentioning
confidence: 99%
“…Marques et al, 2003;Barros-Alves et al, 2013;Guerao et al, 2014). According to phylogenetic analysis, Clark and Ng (2010) suggested that the genera Domecia, Quadrella Dana, 1851, Tetralia Dana, 1851and Trapezia Latreille, 1828 are nested in one clade that is defined by the absence of seta 3.5 and seta 3.4 on the third endopodal segment of the second maxilliped (for details, see Clark and Guerao, 2008), and should be according to a synapomorphy defines the Domecia + Tetralia + Trapezia clade: the presence of one subterminal seta on the distal endopod segment of the maxillule (vs. two subterminal setae).…”
Section: Discussionmentioning
confidence: 99%
“…First zoeal stage of Cataleptodius parvulus (Fabricius, 1793) and Xanthodius denticulatus (White, 1848) (Decapoda: Brachyura): larval evidences and systematic position (Barros‐Alves et al., )…”
Section: Latin America: a Living Laboratory For Evo‐devo Researchmentioning
confidence: 99%
“…Pilumnus Leach, 1815 comprises about 150 species (Ng et al, 2008;Magalhães et al, 2021), popularly known as "hairy crabs" because they have many setae distributed over the carapace and/or pereiopods. These crabs are common in many coastal environments (e.g., coral reefs [Garth, 1984;Giraldes et al, 2015], rocky shores [Kyomo, 1999;Alves et al, 2012;Moraes et al, 2015], unconsolidated bottom [Melo et al, 2000;Ng, 2000] and in association with invertebrates [Lindberg & Frydenborg, 1980;Alves et al, 2012b;Alves et al, 2013]), mainly in tropical regions, but also in temperate zones (Takeda & Miyake, 1969;Williams, 1984;Melo, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…As an example of systematic instability, Pilumnus vinaceus A. Milne-Edwards, 1880, previously considered to be a junior synonym of P. dasypodus by Rathbun (1897), was recently considered a valid species after a review based on integrative morphological and molecular data (Magalhães et al, 2021). The knowledge of the larval morphology can be an important accessory tool in the search for solutions to problems of this systematics, as for many other decapod (Barros- Alves et al, 2013;Clark & Cuesta, 2015;Magalhães et al, 2017). In addition, larval forms of these crabs also may contribute to studies that seek to understand the structure of planktonic communities by providing information that allows the identification of its components.…”
Section: Introductionmentioning
confidence: 99%